Assessing and differentiating reading and writing disorders : multidimensional model - Lombardino, Linda J. (Clifton Park, NY : Delmar Cengage Learning, 2012)
'Assessing and differentiating reading & writing disorders : multidimensional model provides a framework for differentiating among various types of reading and writing disorders in order to assist the practitioner in establishing a differential diagnosis. This text introduces a multidimensional model that can be used to create profiles of a learner's strengths and weaknesses using ten skill domains associated with reading and writing.
Includes bibliographical references (p. 215-248) and index.
Keywords: Disabled Children -- education; Learning disorders